1984
DOI: 10.1161/01.res.54.3.277
|View full text |Cite
|
Sign up to set email alerts
|

Canine myocardial reperfusion injury. Its reduction by the combined administration of superoxide dismutase and catalase.

Abstract: SUMMARY. Therapy directed against the toxic effects of reactive oxygen species may reduce the final extent of ischemic injury in otherwise viable tissue irreversibly injured by the abrupt reoxygenation of reperfusion. In four groups of dogs, superoxide dismutase plus catalase (groups I-III) or saline (controls) (group IV) was infused into the left atrium. Group I received the infusion for 2 hours, beginning 15 minutes before occlusion of the left circumflex coronary artery (90 minutes) and ending 15 minutes af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
227
3
10

Year Published

1985
1985
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 839 publications
(255 citation statements)
references
References 37 publications
(34 reference statements)
13
227
3
10
Order By: Relevance
“…The demonstration by Jolly et al (46) that the administration of superoxide dismutase and catalase to dogs with coronary occlusion prior to the onset of reperfusion reduces infarct size, while the failure of these substances to do so when they are administered following the onset of reperfusion, supports the suggestion that reperfusion damage occurs when the previously ischemic heart is reexposed to oxygen.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 83%
See 1 more Smart Citation
“…The demonstration by Jolly et al (46) that the administration of superoxide dismutase and catalase to dogs with coronary occlusion prior to the onset of reperfusion reduces infarct size, while the failure of these substances to do so when they are administered following the onset of reperfusion, supports the suggestion that reperfusion damage occurs when the previously ischemic heart is reexposed to oxygen.…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 83%
“…Studies in a variety of tissues, including the central nervous system (44), the intestine (45), and the myocardium (46) suggest that oxygen-derived free radicals do contribute importantly to ischemic injury. Severe swelling and lysis of mitochondria in cardiac myocytes and vascular endothelial cells have been demonstrated when isolated cardiac tissue was exposed to solutions capable of generating free radicals (38,40,43).…”
Section: Oxygen-derivedfree Radicalsmentioning
confidence: 99%
“…In a model of cardiac ischemia-reperfusion the augmentation of the activities of total SOD and Se-GPx protects from reactive oxygen species-mediated injury [311. SOD and catalase exogenously administered, reduce the cellular lesions caused by myocardial ischemia-reperfusion in dogs [32]. Ldpez-Torres et al found that enhanced levels of CuZn-SOD, glutathione reductase, glutathione and ascorbate, are correlated with higher survival of catalase-inhibited frogs [5].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence implicating ROS in the pathophysiology of myocardial infarction is derived from investigations using free radical scavengers. Jolly and coworkers [62] demonstrated that the combination of the antioxidant enzymes superoxide dismutase (SOD) and catalase significantly reduced infarct size in dogs undergoing experimental coronary occlusion and reperfusion, when the infusion started before ischemia or 15 min prior to reperfusion. In contrast, no effect was noted when antioxidant infusion was started 40 min after reperfusion, suggesting that free radical-mediated injury is an early event [62].…”
Section: Generation Of Reactive Oxygen Species (Ros) and The Post-infmentioning
confidence: 99%
“…Jolly and coworkers [62] demonstrated that the combination of the antioxidant enzymes superoxide dismutase (SOD) and catalase significantly reduced infarct size in dogs undergoing experimental coronary occlusion and reperfusion, when the infusion started before ischemia or 15 min prior to reperfusion. In contrast, no effect was noted when antioxidant infusion was started 40 min after reperfusion, suggesting that free radical-mediated injury is an early event [62]. Other investigators found similar beneficial effects of antioxidant interventions in experimental models of myocardial infarction.…”
Section: Generation Of Reactive Oxygen Species (Ros) and The Post-infmentioning
confidence: 99%